2017
DOI: 10.1111/jgs.15077
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Trajectory Changes Over 20 Years Before Dementia Diagnosis: A Large Cohort Study

Abstract: Objective Longitudinal studies have shown an increase in cognitive decline many years prior to clinical diagnosis of dementia. We sought to estimate changes, relative to “normal” aging, in the trajectory of a global cognitive function test - the Cognitive Abilities Screening Instrument (CASI). Design A cohort of cognitively intact elderly participants, assessed biennially for dementia for up to 20 years. Setting Community dwelling elderly enrolled in a health maintenance organization. Participants Four t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 46 publications
(144 reference statements)
4
40
0
Order By: Relevance
“…These findings are in line with previous work suggesting that person-specific factors such as genetics and comorbidity may contribute to differences in trajectories prior to death (Wilson et al, 2007;Fabbri et al, 2016;Gerstorf and Ram, 2013). We extend previous studies of competing risks for dementia and death (Li et al, 2017;Prince et al, 2014) by studying two types of dementia disorders, AD and VaD. Although, similar associations were found between the memory groups and AD or VaD risk, the predictors of AD and VaD were different, where female gender and APOE ε4 were risk factors for AD but not for VaD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in line with previous work suggesting that person-specific factors such as genetics and comorbidity may contribute to differences in trajectories prior to death (Wilson et al, 2007;Fabbri et al, 2016;Gerstorf and Ram, 2013). We extend previous studies of competing risks for dementia and death (Li et al, 2017;Prince et al, 2014) by studying two types of dementia disorders, AD and VaD. Although, similar associations were found between the memory groups and AD or VaD risk, the predictors of AD and VaD were different, where female gender and APOE ε4 were risk factors for AD but not for VaD.…”
Section: Discussionsupporting
confidence: 92%
“…This long preclinical stage provides a critical window for intervention and suggests that thorough neuropsychological assessments are important for early detection. Some studies have observed accelerated decline in multiple cognitive functions in the prodromal phase, starting 3-6 years before clinical symptoms (Albert et al, 2014;Amieva et al, 2004;Cloutier et al, 2015;Li et al, 2017;Wilson et al, 2011). These studies have followed initially cognitively normal individuals longitudinally and examined if an accelerated cognitive rate of change precedes clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, previous modeling studies have reported different disease progression rates depending on disease severity, [12][13][14] the prediction of disease onset time, 15 and the impact of biomarkers on the disease course. 14,[16][17][18] In addition, our model is based on the CDR-SB, which is one of the most widely used dementia staging systems, and represents a validated, well-described, and reliable measure of disease progression. 19,20 The CDR-SB has the advantage of being able to measure changes precisely over time from the preclinical stage to the end state of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Using data from the Adult Changes in Thought (ACT) study, a longitudinal cohort study1 of a US population with ongoing enrolment and biannual visits, Li and colleagues assessed changes in cognitive trajectory and timing of accelerated cognitive decline relative to normal ageing in 4315 people. Item Response Theory (IRT) scores of the Cognitive Abilities Screening Instrument (CASI) were used to estimate cognitive trajectories.…”
Section: Methodsmentioning
confidence: 99%